HISTOMORPHOMETRIC INVESTIGATIONS OF SPONTANEOUS CANINE MAMMARY GLAND TUMOURS (TRAKIA JOURNAL OF SCIENCES, 2025)
Histomorphometric analysis was performed on preparations of 18 spontaneous canine mammary epithelial neoplasias (fibroadenoma (n=6), tubulopapillary carcinoma (n=6) and solid carcinoma (n=6). Computer histomorphometric analysis of cell nuclei was performed using a digital microscope and morphometric analysis software (Image Pro PlusÒ v.4.5 Media Cybernetics, Silver Spring, MD, USA).  The studied morphometric parameters were mean nuclear area (MNA, μm2), mean nuclear perimeter (MNP, μm) and mean nuclear diameter (D mean, μm). The analysis of our results shows that there are reliable statistical differences between benign and malignant mammary neoplasms. In this regard, histomorphometric analysis can be used to differentiate benign from malignant mammary neoplasias in the bitch. On the other hand, however, statistical analysis shows that this study does not allow differentiation between malignant mammary neoplasms.